Wheat Grain Yield Increase in Response to Pre-Anthesis Foliar Application of 6-Benzylaminopurine Is Dependent on Floret Development - Zheng, Chunfeng (PLoS One, 2016)
Wheat yield is largely determined during the period prior to flowering, when the final numbers of fertile florets and grains per spike are established. The aim of this study was to assess the dynamics of floret primordia development in winter wheat in response to pre-anthesis application of a synthetic cytokinin, 6-benzylaminopurine (6-BA). We conducted an experiment in which two foliar spray treatments were applied (water or 6-BA) to Chinese winter wheat at 25 days after jointing during two growing seasons (2012–2013 and 2013–2014). Both the final grain number per spike and grain yield at maturity exhibited remarkable increases in response to the 6-BA treatment. Application of 6-BA increased the number of fertile florets in basal spikelets and, to a greater extent, in central spikelets. The mechanism by which 6-BA application affected the final number of fertile florets primarily involved suppression of the floret abortion rates. Application of 6-BA considerably reduced the abortion rates of basal, central and apical spikelet florets (by as much as 77% compared with the control), as well as the degeneration rates of basal and central spikelet florets, albeit to a lesser degree. The effect of 6-BA application on the likelihood of proximal florets being set was limited to the distal florets in the whole spike, whereas obvious increases in the likelihood of grain set under 6-BA treatment were observed in distal florets, primarily in central spikelet positions. The results of this study provide important evidence that 6-BA application to florets (final fertile floret production) results in an increased grain yield.